Declining Social Solidarity Between Microbus Drivers Among the Community of Tataaran II Village, South Tondano District, Minahasa Regency - Romi Mesra; Elisabet Sianturi; Paulus Robert Tuerah (LANGGAM: International Journal of Social Science Education, Art and Culture, 2023)
This study aims to determine the extent to which social solidarity influences fellow microbus drivers in Tataaran II Village, Tondano Selatan District, Minahasa Regency. The research method used is qualitative research by collecting data based on direct observation and interviews with several informants and direct documentation. The general results of the research show that the sense of social solidarity among fellow microbus drivers has a derivation factor from their own nature which makes it a challenge to develop and maintain this sense of social solidarity; Some passengers were not aware of their actions which sparked disputes between microbus drivers, decreased mutual understanding of one another or lack of cooperation among microbus drivers, and attitudes of prioritizing personal interests rather than public interests.